DO SUL DE MATO GROSSO AO MATO GROSSO DO SUL: REGIÃO E HISTORIOGRAFIA EM TORNO DA OBRA DE JOSÉ DE MELO E SILVA - Fiuza, Wagner Henrique Neres (2017)
The research aimed to discuss different nuances related to the proper name of José de Melo e Silva, whether in relation to the different ways of narrating his life, or in relation to the trajectory of his texts, that began to exercise distinct functions throughout their uses in different fields. His texts Fronteras Guaranis (1939) and Canaã do Oeste (1947), spanned both the rise and fall of the Estado Novo (1937-1945) as well as his political projects of occupation and settlement in the West and the southern portion of Mato Grosso. In addition, they also show an opinion about before and after the creation of the Federal Territory of Ponta Porã (1942-1945). Received timidly in the intellectual field and also in the political field, decades later his texts were involved in the commemoration of the 10 years of founding of Mato Grosso do Sul, with the reverse order of publications: first Canaã do Oeste (1989) and, more later, Fronteiras Guaranis (2003). These processes demarcated the status of patron of the Historical and Geographical Institute of Mato Grosso do Sul (IHGMS), and its repositioning in the field of regionalist knowledge production. To discuss these uses and misuses of texts, we use concepts such as discourse, function-author, representation, field and region. The perception of trajectories of an author and his texts that find diffused paths, submitted to different discursive, political and historical processes, have shown us the need to work with different temporalities, either in the first writing or in the republishing of the works in different times, since each Writing a text is the rewriting of the history of the text, its author and the meanings printed in his words.